2022
DOI: 10.1148/radiol.211986
|View full text |Cite
|
Sign up to set email alerts
|

MRI Radiomics Model Predicts Pathologic Complete Response of Rectal Cancer Following Chemoradiotherapy

Abstract: GASTROINTESTINAL IMAGINGF or patients with locally advanced rectal cancer (LARC), neoadjuvant chemoradiotherapy (nCRT) followed by total mesorectal excision is currently the standard treatment (1); however, the treatment response varies considerably, from no tumor regression to pathologic complete response (pCR). Following nCRT, approximately 10%-25% of patients achieve pCR, histopathologically showing no residual tumor (2). Considering the surgical complications and excellent long-term outcomes with nCRT alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 33 publications
2
78
0
2
Order By: Relevance
“…The 21 included studies were published between 2018 and 2022. More than half of the studies (11/21) were based on a population from China ( 34 44 ), three from South Korea ( 45 47 ), three from Italy ( 48 50 ), two from the USA ( 51 , 52 ), one from Brazil ( 53 ), and one from Belgium ( 54 ). Two studies were prospective, and all the remaining studies (19/21) had a retrospective design.…”
Section: Resultsmentioning
confidence: 99%
“…The 21 included studies were published between 2018 and 2022. More than half of the studies (11/21) were based on a population from China ( 34 44 ), three from South Korea ( 45 47 ), three from Italy ( 48 50 ), two from the USA ( 51 , 52 ), one from Brazil ( 53 ), and one from Belgium ( 54 ). Two studies were prospective, and all the remaining studies (19/21) had a retrospective design.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research mostly defined the study endpoint as pCR after LARC treated with nCRT [9,10], but in practice, there are still difficulties in implementing methods including watch and wait and endoscopic transanalresection, even after achieving clinical complete remission (cCR); most patients still undergo TME surgery. Due to the excellent prognosis, patients defined as having a good response, including pCR and stage yp I patients, are the population with the greatest benefit after nCRT, but this population has rarely been studied, and no reliable predictive models are available.…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing minimal residual tumors after neoadjuvant chemoradiotherapy and predicting treatment effectiveness remain challenges in CRC [114]. Kim et al [115], in a study aimed at identifying pathological complete response (pCR, defined as ypT0), have shown that a radiomics model based on T2 WI performs better than radiologists (AUC, 0.82 vs. 0.74; sensitivity, 80.0% vs. 15.6%). Several studies [15,116,117] have developed radiomic models to predict pCR (defined as ypT0N0), with AUCs of 0.812-0.89 [116,117].…”
Section: Treatment Response Of Colorectal Cancermentioning
confidence: 99%